Influence of Product Quality, Service Quality and Service Facilities on Passenger Satisfaction Soekarno-Hatta International Airport (Case Study on Luggage Service at The Airport) - Nugraha, Setiya; Pahala, Yosi; Mustikasari, Mustikasari (Dinasti International Journal of Management Science, 2024)
This study was conducted along with the increasing number of air passengers at Soekarno-Hatta International Airport so that it must be supported by optimal services and still ensure flight safety and security. This study aims to analyze the effect of product quality, service quality, and service facilities on passenger satisfaction at Soekarno-Hatta International Airport, especially on baggage services. This study uses a quantitative approach with a survey method, where data is obtained through questionnaires distributed to 150 passengers at Soekarno Hatta Airport. Data analysis was carried out with validity tests, reliability tests and hypothesis tests to test the effect of product quality, service quality, and service facilities on passenger satisfaction. The results of the study showed that the three variables, namely product quality, service quality, and service facilities, significantly have a positive effect on passenger satisfaction. Of the three variables, service quality has the most dominant effect on passenger satisfaction in baggage services. These findings indicate that improvements in aspects of service quality, such as speed, security, and complaint handling, are needed to improve passenger satisfaction. The practical implications of this study confirm that the management of Soekarno-Hatta International Airport needs to focus on improving the quality of service and management of baggage service facilities to improve overall passenger satisfaction. Improving product quality should also not be ignored, because passengers demand security and comfort in using baggage services.